Revisiting endosulfan - Dilip Gude; Dharam Pal Bansal (Journal of Family Medicine and Primary Care, 2012)
Endosulfan toxicity could precipitate gargantuan jeopardy and may result in irreversible and fatal damage. The spectrum of involvement may range from mild nausea, vomiting, and anxiety to intractable seizures and multiorgan damage resulting in death. We report a case of endosulfan poisoning complicated by multi-organ dysfunction, cardiac arrest, and death.